PENINGKATAN KEMAMPUAN MENULIS TEKS EKSPOSISI DENGAN METODE MIND MAPPING - Abidin, Zaenal (sarasvati, 2021)
This study aims to describe the increase in the ability to write exposition text using the mind mapping method in class X SMK Negeri 3 Berau. This research is classified into classroom action research (Clasroom Action Reaserch) which consists of two cycles. Each cycle is carried out in three stages, namely: (a) planning, (b) action / observation, (c) reflection. This research data uses descriptive qualitative data and quantitative data. Qualitative data were obtained from observation sheets and field note sheets in each action implementation and quantitative data were obtained from the final test of each cycle. The data collection techniques used were observation and exposition text writing test. The results showed that the application of the mind mapping method as a learning method was very effective in improving the ability to write exposition text of class X students of SMK Negeri 3 Berau. Based on the results of the assessment, both the process assessment and the assessment of the results of writing the exposition text, the application of the mind mapping method was declared successful. From the results of the assessment based on the set intervals, the students' skills in writing the exposition text got satisfactory results. All students studied got a score of 65 and above. Finally, it can be concluded that the mind mapping method can improve the ability to write exposition text for tenth grade students of SMK Negeri 3 Berau.